Effecacy evaluation of treatment and rehabilitation in patients with the first psychotic episode with biological rhythms - Zhyvotovska, Liliya; Boiko, Dmitriy; Bodnar, Lesya; Shinder, Vyacheslav (ScienceRise: Medical Science, 2017)
The aim of this research was in evaluation of efficacy of treating-rehabilitating arrangements in patients with the first psychotic episode taking into account biological rhythms. Materials and methods: The study included 130 patients with the first psychotic episode. The characteristic of biological rhythms was carried out according to Estberg scale, evaluation of life quality according to SF-36 scale. Results: The psychoeducational program was realized in stages and included informational (explanation to patient and relatives of the necessity to take medicaments and visit doctors, the features of disease manifestation, prognosis), therapeutical (prevention of autoaggressive tendencies), social (overcoming of patient’s stigmatization, formation of support by family members) and final stages (formation of new forms of reaction in the case of aggravation). According to the distribution in groups of daily working activity, the psychoeducational arrangements with patients of the first group was realized in second half of day, and with ones of the second and third group – in first half. Conclusions: As a result of the study it was established, that the use of clinical protocols of treatment together with psychoeducational program taking into account biological rhythms in patients with the first psychotic episode leads to the improvement of their life quality. So, the further studies in this field are the priority direction in psychiatry to improve the prophylactic, treating and rehabilitating arrangements